1997
DOI: 10.1172/jci119488
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin 1 receptor antagonist (IL-1Ra) is an acute-phase protein.

Abstract: Interleukin 1 receptor antagonist (IL-1Ra) levels are elevated in the blood of patients with a variety of infectious, immune, or traumatic conditions. To examine whether IL1Ra is produced by liver cells with characteristics resembling an acute-phase protein, human primary hepatocytes isolated from liver biopsies and HepG2 hepatoma cells were stimulated with IL-1 ␤ , IL-6, and TNF ␣ . IL-1Ra was present in the supernatants of both cells, with production significantly enhanced by IL-1 ␤ , and by the combination … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
197
1
7

Year Published

1998
1998
2015
2015

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 285 publications
(215 citation statements)
references
References 60 publications
10
197
1
7
Order By: Relevance
“…However, dominant-negative NF-B failed to modify the rosiglitazone-induced enhancement of IL-1Ra secretion in synoviocytes, which demonstrates that this pathway was not primarily involved despite its requirement for cellular activation. Based on previous studies on the human IL-1Ra promoter, one can suggest that rosiglitazone could have affected alternate IL-1-sensitive transacting factors such as CCAAT/enhancer binding proteins or activator protein 1 (60,61). Second, we searched for the possible contribution of PPAR␤/␦, since high-dose rosiglitazone was shown to activate the PPAR-responsive promoter in cells expressing PPAR␤/␦ but not PPAR␥ (19), whereas it inhibited inflammatory genes through activation of the PPAR␤/␦ isotype in macrophages (62).…”
Section: Discussionmentioning
confidence: 99%
“…However, dominant-negative NF-B failed to modify the rosiglitazone-induced enhancement of IL-1Ra secretion in synoviocytes, which demonstrates that this pathway was not primarily involved despite its requirement for cellular activation. Based on previous studies on the human IL-1Ra promoter, one can suggest that rosiglitazone could have affected alternate IL-1-sensitive transacting factors such as CCAAT/enhancer binding proteins or activator protein 1 (60,61). Second, we searched for the possible contribution of PPAR␤/␦, since high-dose rosiglitazone was shown to activate the PPAR-responsive promoter in cells expressing PPAR␤/␦ but not PPAR␥ (19), whereas it inhibited inflammatory genes through activation of the PPAR␤/␦ isotype in macrophages (62).…”
Section: Discussionmentioning
confidence: 99%
“…Supporting this concept is the existence of a splice variant of the IL-1RAcP, which lacks a transmembrane anchor (28)(29)(30). This sIL-1RAcP is synthesized and released by the liver in somewhat the same way IL-1Ra is released by the liver; as an acutephase protein (31). In the report by Smeets and colleagues, overexpression of sIL-1RAcP likely formed a complex of IL-1␤ with sIL-1RII in the extracellular space ( Figure 2C), with the cell surface IL-1RII ( Figure 2D), or possibly with IL-1RI ( Figure 2D).…”
Section: What Accounts For the Differences Between Overexpression Of mentioning
confidence: 99%
“…The mRNA for icIL-1Ra2 was detected in activated fibroblasts, monocytes, neutrophils, and keratinocytes [21]. Finally, icIL-1Ra3 was detected by western blot analysis in cell lysates of LPS-stimulated neutrophils, monocytes, and hepatocytes, and corresponds to an alternative translation initiation product from sIL-1Ra mRNA [22,23].Our previous reports demonstrated that human and mouse primary hepatocytes are able to produce high levels of IL-1Ra in response to inflammatory challenge in vitro [22,24]. Hepatocytes might thus represent an important source of IL-1Ra during liver injury, although this hypothesis has not been formally examined.…”
mentioning
confidence: 98%